1999
DOI: 10.1046/j.1365-2249.1999.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma (IFN-γ) and prostaglandin E2 (PGE2) regulate differently IL-12 production in human intestinal lamina propria mononuclear cells (LPMC)

Abstract: SUMMARYIL-12 modulates Th1 immune response during chronic colitis. Mechanisms regulating IL-12 synthesis in human intestine are poorly understood. The aim of this study was to investigate the effect of IFN-g and PGE 2 on lipopolysaccharide (LPS)-stimulated LPMC IL-12 production. Normal LPMC cultures were run in the presence or absence of IFN-g and/or PGE 2 before LPS stimulation. To examine the role of endogenous PGE 2 on LPS-stimulated IL-12 release, LPMC cultures were added of indomethacin before LPS stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Lamina propria is a major site of mucosal PGE2 production, which has recently been reported to lead to production of IL-10, a key cytokine involved in mucosal tolerance. 5,6,22,24) In agreement with previous studies, 5,24) we observed that LPMC produced PGE2 and IL-10 spontaneously (Fig. 12A-a and c).…”
Section: Fig 8 Effect Of Ogt On Pge2 Levels In the Intestinal Mucossupporting
confidence: 91%
See 1 more Smart Citation
“…Lamina propria is a major site of mucosal PGE2 production, which has recently been reported to lead to production of IL-10, a key cytokine involved in mucosal tolerance. 5,6,22,24) In agreement with previous studies, 5,24) we observed that LPMC produced PGE2 and IL-10 spontaneously (Fig. 12A-a and c).…”
Section: Fig 8 Effect Of Ogt On Pge2 Levels In the Intestinal Mucossupporting
confidence: 91%
“…[1][2][3][4] PGE2 enhances interleukin 10 (IL-10) synthesis and modulates the intestinal immune response to dietary antigen. 5,6) The breakdown of systemic tolerance to luminal antigen is reportedly involved in the development of indomethacin-induced enteropathy. 7) Indomethacin is one of the non-steroidal anti-inflammatory drugs (NSAIDs) that reduce PGE2 production via inhibition of the cyclooxygenases (COXs) 2) , COX-1 and COX-2.…”
mentioning
confidence: 99%
“…The levels of IL-8 and Foxp3 expression were correlated per single cell basis (Fig. 6E) 29 The data suggests that in addition to macrophages, other cells may be important producers of IL-8 in the colon mucosa. In line with this possibility, to our surprise, we have shown that the levels of IL-8 are dramatically higher in Treg cells than the Treg-depleted mononuclear cells (containing macrophages) in the microenvironments of colitis and colon cancer.…”
Section: Foxp3mentioning
confidence: 74%
“…A footprint over a purine-rich sequence at Ϫ155 observed only in resting cells was caused by a specific protein complex, denoted GATA sequence in the IL-12 promoter (GA-12) 3 binding protein (GAP-12), thereby repressing inducible IL-12 p40 gene transcription in monocytes. Interestingly, GAP-12 binding to this site was enhanced by IL-4 and PGE 2 , which have been previously described as potent inhibitors of IL-12 expression (21)(22)(23)(24)(25). Our data suggest a model in which the stimulation of monocytes and macrophages with bacterial cell wall components such as LPS leads to the displacement of the GAP-12 repressor and subsequently to the binding of activating transcription factors such as p50/p65, C/EBP␤, and PU.1.…”
mentioning
confidence: 74%